Experimental Research of the Coagulation Process of Exhaust Gases under the Influence of Ultrasound - Adil S. Kadyrov; Bauyrzhan K. Sarsembekov; Aleksandr A. Ganyukov; Zhanara Z. Zhunusbekova; Kuanysh N. Alikarimov (Communications - Scientific letters of the University of Zilina, 2021)
The authors propose the use of ultrasonic radiation to clean the exhaust gases of internal combustion engines of the solid particles. An experimental stand and research results are presented, proving the possibility and efficiency of using the process of ultrasonic cleaning of exhaust gases due to the process of the solid particles coagulation. The authors received a corresponding patent, the efficiency of which has been proven by results of the conducted research.